Management of Takayasu arteritis: a systematic review - DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2014)
Assessment of the pattern and extent of arterial involvement and measurement of current disease activity are essential for the management of Takayasu arteritis (TA). Since there is no completed, placebo-controlled, randomized clinical trial, the level of evidence for management of TA is low, generally reflecting the results of open studies, case series and expert opinion. The most commonly used agents include corticosteroids and conventional immunosuppressive agents such as MTX, AZA, MMF and LEF. In patients who remain resistant and/or intolerant to these agents, biologic drugs including TNF inhibitors, rituximab and tocilizumab seem to be promising. Antiplatelet treatment may also lower the frequency of ischaemic events in TA. In the presence of short-segment, critical arterial stenosis, balloon angioplasty or stent graft replacement may be useful. On the other hand, long-segment stenosis with extensive periarterial fibrosis or occlusion requires surgical bypass of the affected segment, which is clearly associated with superior results compared with endovascular intervention. As a general rule, both endovascular intervention and surgical procedures should be avoided during the active phase of the disease. Earlier diagnosis, better assessment of disease activity and future clinical trials will obviously improve the management of TA.
Keywords: management; Takayasu arteritis; Takayasu vasculitis; large vessel vasculitis; LARGE-VESSEL VASCULITIS; GIANT-CELL ARTERITIS; NECROSIS FACTOR THERAPY; DISEASE-ACTIVITY; IMMUNOSUPPRESSIVE TREATMENT; NONSPECIFIC AORTOARTERITIS; PYODERMA-GANGRENOSUM; SURGICAL-TREATMENT; TNF-ALPHA; GLUCOCORTICOID-RESISTANT